A randomized, double-blind, placebo-controlled clinical trial of fluoride varnish in preventing dental caries of Sjögren's syndrome patients. Issue 1 (December 2016) - Xin, Weini; Leung, Katherine; Lo, Edward; Mok, Mo; Leung, Moon
Abstract Background Sjögren's syndrome (SS) patients are prone to caries development due to reduction of salivary flow. Topical fluoride is commonly prescribed for caries prevention. Methods In this 24-month randomized, double-blind, placebo-controlled clinical trial, SS patients were randomly assigned to receive either fluoride varnish or placebo gel quarterly. Development and arrest of caries at the coronal and root surfaces were recorded at 12-month and 24-month and compared to that of the baseline. Effect of fluoride varnish on oral Candida and lactobacilli colonization was explored by comparing baseline oral microbiological assessments to data obtained at 12-month and 24-month. Results Seventy-eight SS patients (mean age = 50 years, 2 men) completed this trial. At 24-month, the mean new coronal enamel caries were 1.6 surfaces in both groups, and new dentin caries were 1.4 and 2.7 surfaces in the fluoride and placebo group respectively (p  > 0.05). Mean arrested caries were 0.6 and 0.7 surfaces for fluoride and placebo groups respectively and that of root caries were 0.3 and 0.1 surfaces (p  > 0.05). The mean oral Candida count was reduced by 30 % in the fluoride group but increased 61 % in the placebo group while no change in oral lactobacilli counts in both groups at 24 months (p  > 0.05). SS patients receiving fluoride varnish were significantly less likely to develop dentin caries (p  < 0.05). In contrast, those with high baseline DMFS scores (p  = 0.05), harbored mixed Candida species (p  < 0.05), or unstimulated whole saliva at low pH (p  < 0.01) were significantly more likely to develop dentin caries. Conclusions Results of this randomized clinical trial did not provide clear evidence to support or refute that quarterly applications of fluoride varnish can prevent development of dental caries in people with Sjögren's syndrome. Trial registration This study was retrospectively registered at the ISRCTN registry (ISRCTN85164658 ) on 9 Sept 2016 and was funded by the Research Grant Council of Hong Kong.